Urban cellular wireless network planning with 3D geographical grid structures - Özyurt, Murat. (Thesis (Ph.D.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2019., 2019)
The largest traffic on the Internet is generated by multimedia content, and the share of wireless mobile access to the multimedia content is ever increasing. The delivery process in the content depends on the type of the content, and whether it requires a strictly time sensitive live session, or it can be delivered on demand, irrespective of time of request. As a general solution in the IP networks, the delivery is taking place as multiple individual transmissions from the source to all receivers, replicating the same content at di erent times, or at the same time if the content is streaming live. In this thesis, we propose an advanced collaborative multicast routing model for delivering bandwidth hungry streaming content such as IPTV to multiple users having low quality wireless connection, with the help of other nearby users having a better connection quality utilizing the wireless mesh network topology. The model reduces the amount of data replication, which causes signifficant overhead in the network transmissions and intermediate computations, improving the overall throughput of the wireless network. An essential issue in wireless mobile networks is where to position the base stations on the network coverage area. We also propose an alternative adaptive mixed path signal propagation estimation model for planning the base station locations in new deployment areas, based on the signal characteristics of existing networks. In doing so, we utilize digital 3D maps of urban areas and signal measurements to train the adaptive model, and to exploit local similarities in cities in order to estimate the signal channel characteristics and calculate the potential base station locations for covering the new area with a speciffic wireless communication technology.
Keywords: Wireless sensor networks.; Computer Communication Networks.; Information storage and retrieval systems.